Evaluating Longitudinal Invariance in Dimensions of Mental Health Across Adolescence: An Analysis of the Social Behavior Questionnaire. (October 2019) - Murray, Aja Louise; Obsuth, Ingrid; Eisner, Manuel; Ribeaud, Denis
Measurement invariance over time (longitudinal invariance) is a core but seldom-tested assumption of many longitudinal studies on adolescent psychosocial development. In this study, we evaluated the longitudinal invariance of a brief measure of adolescent mental health: the Social Behavior Questionnaire (SBQ). The SBQ was administered to participants of the Zurich Project on the Social Development of Children and Youths in up to four waves spanning ages 11 to 17. Using a confirmatory factor analysis approach, metric invariance held for all constructs, but there were some violations of scalar and strict invariance. Overall, intercepts tended to increase over time while residual variances decreased. This suggests that participants may become more willing or able to identify and report on certain behaviors over time. The noninvariance was not practically significant in magnitude, except for the Anxiety dimension where artifactual increases over development would be liable to occur if invariance is not appropriately modeled. Overall, results support the utility of the SBQ as an omnibus measure of psychosocial health across adolescence.